ESG and Internal Control Weaknesses – A Case Study of an Islamic Cooperative Body - Shamsul Anuar, Abd Rahim; Annuar, Nawawi; Ahmad Saiful, Azlin Puteh Salin (RSIS International, 2025)
The purpose of this study is to examine what are some of the weaknesses in a cooperative body administration, that may related to Environment, Social and Governance (ESG) activities. A case study approach was selected for this study by selecting one Islamic cooperative body in Malaysia as a study case. This study found that the selected cooperative has many weaknesses in their internal control procedures. Many errors in recording financial data lead to the fraud opportunity while manual recording of daily transaction contributes to recurring human errors. This indicate that this cooperative body yet to fully exercising ESG framework, particularly the governance pillar of the framework. This study however limited to only one organization and thus, its findings need to be generalised with precautions.